2004
DOI: 10.1103/physrevlett.93.256101
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Electronic States on Si(111)-(7×7)through Short-Range Attractive Force with Noncontact Atomic Force Spectroscopy

Abstract: We experimentally reveal that the short-range attractive force between a Si tip and a Si(111)-7 7 surface is enhanced at specified bias voltages; we conduct force spectroscopy based on noncontact atomic force microscopy with changing bias voltage at a fixed separation. The spectra exhibit prominent peaks and a broad peak, which are attributed to quantum mechanical resonance as the energy levels of sample surface states are tuned to those of the tip states by shifting the Fermi level through changing bias volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…63 In particular, above a Si adatom, they found a narrow peak growing with decreasing d superposed on the usual parabolic dependence around the plotted minimum of −∆f 1 (V b ) in their Fig. 1, i.e.…”
Section: Short-range Electrostatic Forces a Evidence And Previomentioning
confidence: 85%
“…63 In particular, above a Si adatom, they found a narrow peak growing with decreasing d superposed on the usual parabolic dependence around the plotted minimum of −∆f 1 (V b ) in their Fig. 1, i.e.…”
Section: Short-range Electrostatic Forces a Evidence And Previomentioning
confidence: 85%
“…The apparent atomic contrast is about 1.5 Hz and close to the detection limit. A clean tip is known to be appropriate for imaging silicon surfaces because of the strong chemical interaction between the Si atoms at the tip apex and silicon atoms in the surface 8,42 and has been proposed to yield a good chemical contrast also on CaF 2 (111). 34 It has, however, also been pointed out that a silicon based tip generally exhibits a considerably smaller interaction with the ionic surface than a polar tip.…”
Section: (C)mentioning
confidence: 99%
“…Noncontact atomic force microscopy (NC-AFM) has greatly succeeded in imaging and manipulating a variety of surfaces of metals, 1, 2 semi-metals, [3][4][5] semiconductors, [6][7][8][9][10] and insulators. [11][12][13][14] In particular, atom-resolved imaging on terraces 15 and at step edges [16][17][18] on CaF 2 (111) that is the surface of interest for this study, is well established and understood by extensive theoretical modelling.…”
mentioning
confidence: 99%
“…4), it is evidently more symmetric than in [17]. Arai and Tomitori [25] have recently shown that force interactions are also a function of bias. Figure 4d)-f) shows constant-height images at a different tip bias of -60 mV.…”
mentioning
confidence: 99%